An improved desaturation short-circuit protection method for SiC power modules. (April 2022) - Qin, Haihong; Hu, Haoxiang; Huang, Wenxin; Mo, Yubin; Chen, Wenming
Abstract: Silicon Carbide (SiC) MOSFET devices have smaller chip size and higher current density than Si counterparts, which results in the limited short-circuit capability of SiC power modules. The presently used protection circuit is actually conventional desaturation protection method, which is very suitable for IGBT modules. But this conventional protection circuit has relatively slow response, and cannot be directly used in SiC modules due to its higher di/dt and weaker ruggedness compared to IGBT modules. So we propose an improved desaturation protection method. We first analyse the short-circuit process to obtain the short circuit characteristics of SiC MOSFET. Then, we give the principle of the improved desaturation protection method, and present the comparison between the conventional protection circuit and the improved one. At last, short-circuit protection tests under HSF and FUL faults have been conducted to verify the improved desaturation protection circuit. The experimental results show that the improved desaturation protection circuit has a faster response than the traditional one, and can make SiC modules work reliably.